Thoughts on Starting the CODATA Data Science Journal - John Rumble (Data Science Journal, 2023)
This essay discusses some of the considerations that led to the founding of the [CODATA] Data Science Journal. Three factors were most relevant to the founding. First, there was a need to have a more formal publication mechanism for the papers given at the biennial CODATA International Conferences. Second, there was a pressing need for data science advancements made in one area of scientific data work to be shared with other scientific disciplines. Lastly the increasing number of scientists interested in data, throughout science, and throughout the world, required a more convenient publication outlet. Thus arose the Data Science Journal.